Integrated approach of pond based farming systems for sustainable production and income generation (Bangladesh Journal of Agricultural Research, 2010)
Integrated farming with poultry, fish and crops can play a significant role in increasing manifold production, income, and nutrition and employment opportunities of rural populations. The research work was carried out at nine farmers’ ponds covering area of 0.12 ha each in Farming Systems Research and Development (FSRD) site, Goyeshpur, Pabna during the year 2000-01 to 2002-03 to assess integrated pond based production, income and employment opportunity of the rural farm households. Three different components like fish, poultry and pattern based vegetables production were employed in the investigation. The results indicated that in integrated pond management, two additional enterprises viz., poultry and year round vegetables exhibited encouraging production over traditional management. The average fish production obtained from integrated pond management was 330.92% higher over the traditional management. The total economic return in terms of gross return and gross margin achieved from integrated pond management was Tk.59 133 and 38684 which were 1297.94 and 1496.53% higher over traditional pond management. The utilization of family labour round the year in pond based integrated production system contributed to improve the production as well as to create employment opportunity for income generation. The overall results revealed that the integrated pond management with poultry, fish and vegetables was an excellent approach for sustainable production, income generation and employment opportunity of the resource poor rural households. Key Words: Pond based farming systems; production; income generation; employment opportunity. DOI: 10.3329/bjar.v34i4.5834Bangladesh J. Agril. Res. 34(4) : 577-584, December 2009